Sialuria-Related Intellectual Disability in Children and Adolescent of Pakistan: Tenth Patient Described has a Novel Mutation in the GNE Gene - Ishtiaq, Hina; Siddiqui, Sonia; Nawaz, Rukhsana; Jamali, Khawar S.; Khan, Abdul Ghani (CNS & Neurological Disorders - Drug Targets, 2020)
Background: Sialuria is a rare inborn error of metabolism caused by excessive synthesis of sialic acid due to the mutation in the binding site of the cytidine monophosphate-sialic acid of UDPGlcNAc 2-Epimerase/ManNAc Kinase (GNE/MNK). Objective: This is the first study investigating the molecular basis of neuronal disorders exhibiting sialuria in Pakistani children/adolescents. Methods: The current study genotyped GNE SNPs rs121908621, rs121908622 and rs121908623 by using PCR, RFLP, and DNA sequencing methods. Socioeconomic and clinical histories were also recorded. Results: Our data suggest that clinical symptoms and financial status play a significant role in conferring sialuria related Intellectual Disability (ID). SNP: rs121908623 showed G/A substitution (R263Q) in the GNE gene. Conclusion: We have identified one case study in Pakistan, so this makes our research a leap forward towards the identification of the 10th case study worldwide.
Keywords: arginine (R)